Estudo da influência da oxidação a plasma nas propriedades tribológicas da liga metálica TI-6AL-4V. - Siqueira, Rafael Coelho (2019)
The oxidation thermal or the plasma on the surface of the titanium mean to improve the surface resistance to corrosion and abrasive wear, increase the surface hardness and increase the thickness of the formed oxide. Oxidation treatment is used to improve the biocompatibility of the Ti-Al-4V alloy. This report wants to determine the effect of plasma oxidation on the tribological properties of the Ti-6Al-4V metal alloy and the effect that the pressure and temperature sputtering parameters used during the treatment could on the surface of the oxidized samples. Samples have a metallographic preparation on the surface until a mirror finish is obtained, the samples are cleaned and dried and then it is to put to inside the plasma reactor that using a pulsed DC electric source. First the sputtering is carried out on the samples and the oxidation treatment is carried out in sequence. During the sputtering, two proportions of gases were used: 50% Ar and 50% H2, and 80% Ar and 20% H2. For the oxidation treatment the gas ratio of 60% Ar and 40% O2 was used. The pressures used during the treatment were 1.65 Torr and 3.75 Torr. The temperatures used were 480 ° C, 520 °C, 670 °C and 705 °C. The treated samples and the untreated material were characterized by the Vickers hardness test and scanning electron microscopy and abrasive micro-wear. It was observed that the variation of the gas proportions in the sputtering and pressure during the treatment had no an expressive impact of variation with respect to the thickness of the formed oxides, surface hardness and resistance to the micro-abrasive abrasive. About to temperature, this shows a better influence on the thickness of the oxide formed, the hardness of the surface and the resistance to abrasive micro-wear. Average variation in film growth thickness was of approximately 1,2 to 6,8 μm. The hardness of the treated surface became higher than that of the untreated material under all treatment conditions and the reduction of surface abrasive micro-wear occurred.